PENINGKATAN KETERAMPILAN BERBICARA DENGAN MENGGUNAKAN MODEL COLLABORATIVE LEARNING: STUDI PENELITIAN TINDAKAN KELAS - Guswita, Reni (Information Technology Education Department, 2024)
Indonesian language learning in elementary schools aims to improve students' ability to communicate in Indonesian language properly and correctly, both orally and in writing. This research is a class action research, which consists of two cycles. Each cycle consists of planning activities, action implementation, observation and reflection. Data collection techniques in this study were observation, tests and documentation. The research subjects were fifth grade students at SD N 104/II Muara Bungo with a total of 20 students. The results of this study show that the learning process of educators during the learning process using the Collaborative Learning model in cycle I has reached 62.5%. Furthermore, in cycle II it has been carried out very well, namely with a percentage value of 86.1%. Students during the learning process using the Collaborative Learning model in cycle I reached 66.53%. Furthermore, in cycle II it reached 78.03%. Assessment of students' speaking skills using the Collaborative Learning model in cycle I reached 66.15%. While in cycle II students' speaking skills reached 79.95%. Based on the results of this study, it can be concluded that the use of the Collaborative Learning model can improve the speaking skills of students in class V.